Work-based Learning Scenario in Electronics Polytechnics Vocational Education Politeknik Negeri Malang Incorporate with Preparation for Future Workforce 4.0 - Andriani Parastiwi, Tundung Subali Patma, Supriatna Adhisuwignjo, Dodi Maulana (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Abstract—Work-based Learning is a transition from education in institutions to carriers. It is combines institutional learning with industrial learning and creates an integrated experience for the student as future industrial workforce 4.0. This paper discusses about work-based learning scenario applied in electronics polytechnics educations in which students will learn at campus and industries to complete their courses. This paper also emphasis the work-based learning scenario in Indonesia that have been used in advance diploma courses in Politeknik Negeri Malang. To make sure work-based learning succeed, cooperation from all three parties, namely the student, the educational institution and the industrial employer, is important. Implementation of work-based learning had been studied by researchers locally and abroad to identify the parties involved that make the work-based learning successful. Scenario and how its implementation in campus was observed. It concludes with a scenario of work-based learning can be served with work-based learning can be done in: 1)institution; 2)institution or industry; 3)industry. Whereas the purpose work-based learning is to: 1)learning about industrial work; 2)learning through industrial work; and 3)learning for industrial work.